The effects of hysteroscopy and laparoscopy for scar diverticulum resection and suture on blood loss, operation time and antibiotic time - Weifeng Li; Tiecheng Lin; Yong Xie; Lijiang Xu; Yangping Chen; Yuyuan Zhu; Xia Dong; Pei Cheng; Chunxiang Duan (Taylor & Francis Group, 2022)
AbstractTo evaluate the effect of hysteroscopy and suture on uterine scar diverticulum (CSD) after caesarean section and its influence on blood loss, operation time and antibiotic time. Eighty-nine patients with CSD were divided into observation group (n = 41 cases) and control group (n = 48 cases). Control group received laparoscopic scar diverticulum resection and suture, while the observation group received hysteroscopic resection of scar diverticulum. The operation time of the observation group was longer, while the bleeding volume and antibiotic administration time were significantly lower. The surgical treatment efficiency of the observation group (97.56%) was significantly higher. After treatment, the observation group's diverticulum repair indexes (width, depth and lower uterine muscular layer thickness) were better than those of the control group (p<.05). Hysteroscopic resection of scar diverticulum in CSD reduces intraoperative blood loss and the risk of complications, shortens time of antibiotic administration, and promotes diverticulum repair.Impact StatementWhat is already known on this subject? Uterine scar diverticulum (CSD) after caesarean section, also called postoperative uterine incision defect (PCSD), is due to poor healing of the uterine incision after caesarean section.What do the results of this study add? Hysteroscopic resection of scar diverticulum in CSD has a significant clinical effect, which can effectively reduce intraoperative blood loss and the risk of complications, shorten the time of antibiotic administration, and promote diverticulum repair.What are the implications of these findings for clinical practice and/or further research? Clinical effect of hysteroscopic resection of scar diverticulum in CSD is significant.